Effects of surface sterilization of fertile eggs on the yolk microbiota during the chicken embryo development - Ding, Peng; He, Xi; Li, Minxi; Jiang, Sai; Peng, Yanmei (Frontiers in Veterinary Science, 2024)
Surface sterilization of the fertile eggs is a common process for commercial broiler breeding to avoid pathogenic bacterial infections before incubation. However, it is also possible to remove the beneficial microbes that might contribute to the development of chicken embryos. Thus, we established a model to mimic surface sterilization in the laboratory by rubbing fertile eggs with 70% ethanol and investigated the effect of eggshell surface sterilization on the yolk microbiota and its potential role in chicken (Gallus gallus) embryo development. In total, 460 Ross 308 fertile eggs were randomly divided equally into the eggshell surface sterilized group (CS, commercial egg sterilization group) and the eggshell surface unsterilized group (CC, commercial egg control group). The shell surface of group CS was sterilized with 70% alcohol before incubation (E0, embryonic stage), while that of group CC was not sterilized before incubation. At each sampling day (E0, E07, E15, and E21), 24 fertile eggs from each of the two groups were randomly selected to collect the yolk samples and weigh the embryos. The results showed that the surface sterilization of eggshells before incubation improved the development of chicken embryos from E15 to E21 but reduced the diversity of the yolk microbiota. In the whole process of embryogenesis, the relative abundance of Firmicutes, Bacteroidetes, and Actinobacteria in the egg yolk of group CS was lower than that of group CC before incubation. Indeed, the surface sterilization of fertile eggs significantly reduced the relative abundance of Staphylococcus saprophyticus and other pathogenic bacteria in the yolk, which may result in the better development of chicken embryos.